An Argon Gas Scintillation Counter with Uniform Electric Field - Conde, C. A. N. (1975)
A new type of gas proportional scintilla- tion counter with uniform electric field is described. This counter-is the scintillation counter analog of the Frish ionization chamber. Its principle is discussed and the properties experimentally studied using pure argon. Ener- gy resolutions of 1.9% were obtained for 8.1 MeV alpha particles. Some results concerning the interpretation of the mechanism of the se- condary scintillation are discussed